2013
DOI: 10.1152/japplphysiol.00586.2012
|View full text |Cite
|
Sign up to set email alerts
|

Preventive role of exercise training in autonomic, hemodynamic, and metabolic parameters in rats under high risk of metabolic syndrome development

Abstract: Moraes-Silva IC, Mostarda C, Moreira ED, Silva KAS, dos Santos F, de Angelis K, Farah VMA V, Irigoyen MC. Preventive role of exercise training in autonomic, hemodynamic, and metabolic parameters in rats under high risk of metabolic syndrome development. J Appl Physiol 114: 786 -791, 2013. First published January 17, 2013 doi:10.1152/japplphysiol.00586.2012.-High fructose consumption contributes to metabolic syndrome incidence, whereas exercise training promotes several beneficial adaptations. In this study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
1
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 37 publications
6
31
1
3
Order By: Relevance
“…The fructose overload induced glucose intolerance and/or insulin resistance, unfavorable changes in lipid profile, as well as an increase in adipose tissue in male and female adults and developing animals [6, 7, 8, 21]. Indeed, our study showed that physical training was able to prevent these metabolic alterations induced by fructose overload as previous reported by others studies [5, 17, 34, 35, 36]. …”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The fructose overload induced glucose intolerance and/or insulin resistance, unfavorable changes in lipid profile, as well as an increase in adipose tissue in male and female adults and developing animals [6, 7, 8, 21]. Indeed, our study showed that physical training was able to prevent these metabolic alterations induced by fructose overload as previous reported by others studies [5, 17, 34, 35, 36]. …”
Section: Discussionsupporting
confidence: 87%
“…Moderate-intensity exercise training (40–60% maximal running speed, 0% inclination) was performed on a treadmill once a day at the same time every day, 5 days/week during 8 weeks, as described in detail elsewhere [5]. The protocol was initially carried out with the concurrent administration of fructose.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations